2017
DOI: 10.3168/jds.2016-12529
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the variability and repeatability of gonadotropin-releasing hormone–induced luteinizing hormone responses in dairy cows within a synchronized ovulation protocol

Abstract: The primary objective was to determine the variability and repeatability of GnRH-induced LH responses. The secondary objective was to evaluate the associations among plasma LH, FSH, estradiol (E2), and progesterone (P4) concentrations. One hundred lactating Holstein cows (35 primiparous, 65 multiparous) were initially subjected to a presynchronization protocol (d 0, PGF; d 3, GnRH) followed 7 d later by Ovsynch (d 10, GnRH; d 17, PGF; 56 h later, GnRH) and timed artificial insemination 16 h after the last GnRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…This study demonstrated LH urinary excretion in cows after administration of GnRH. A transient increase was observed in urine LH levels following the increase in plasma LH concentrations in all cows tested, and ovulation was confirmed 48 hr after GnRH administration, as per previous reports [6][7][8][9]. In our experiment, the peak urinary LH-urinary creatinine ratio was observed between 3 and 6 hr (median 5 hr) after GnRH administration in each cow, which was approximately 3 hr later than that of the plasma LH concentration.…”
supporting
confidence: 91%
“…This study demonstrated LH urinary excretion in cows after administration of GnRH. A transient increase was observed in urine LH levels following the increase in plasma LH concentrations in all cows tested, and ovulation was confirmed 48 hr after GnRH administration, as per previous reports [6][7][8][9]. In our experiment, the peak urinary LH-urinary creatinine ratio was observed between 3 and 6 hr (median 5 hr) after GnRH administration in each cow, which was approximately 3 hr later than that of the plasma LH concentration.…”
supporting
confidence: 91%
“…Samples were placed on ice upon collection and centrifuged at 1,500 × g for 20 min at 4°C, and plasma was harvested and stored at −20°C until being assayed for progesterone (P4). Plasma P4 concentrations were quantified at Endocrine Lab Services (University of Saskatchewan, Saskatoon, SK, Canada) using a commercial solid-phase RIA kit (ImmuChem; MP Biomedicals LLC, Orangeburg, NY) as in Gobikrushanth et al (2017). The intra-assay coefficients of variation averaged 8.6% for low and 13.0% for high reference samples, the interassay coefficients were 11.7% for low (mean = 0.96 ng/mL) and 15.7% for high (mean = 11.40 ng/mL) reference samples, and the assay sensitivity was 0.11 ng/mL.…”
Section: Postpubertal Phasementioning
confidence: 99%